Pengaruh Faktor-Faktor Knowledge Management Melalui Attitude yang Dimoderasi oleh Kepemimpinan dan Budaya Organisasi terhadap Intention (Studi Kasus pada PT PLN (Persero) UIP JBT) - Pratama, Reza Adit (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the effect of Extrinsic Reward, Social Trust, Sense of Self-Worth, and Expected Association on Attitude toward Knowledge Sharing Behavior, as well as the effect of Attitude toward Knowledge Sharing Behavior and Subjective Norm on Intention to Share Knowledge at PT PLN (Persero) UIP JBT. This study uses a quantitative approach with a verification research type. The data collection technique was carried out by distributing questionnaires to 147 employees obtained using the Slovin method from a population of 285 employees. The sampling technique used was non-probability sampling with the accidental sampling method. Data analysis was carried out using the multiple regression method (Multiple Regression Analysis), which requires metric scale data (interval). Therefore, the ordinal data obtained were first converted into interval data using the Method of Successive Interval (MSI). The results showed that Social Trust and Expected Association had a significant effect on Attitude toward Knowledge Sharing Behavior, while Extrinsic Reward and Sense of Self-Worth did not have a significant effect. Furthermore, Attitude toward Knowledge Sharing Behavior and Subjective Norm had a significant effect on Intention to Share Knowledge. However, the interaction between Attitude toward Knowledge Sharing Behavior and Subjective Norm had no significant effect on the intention to share knowledge. These findings indicate that building social trust and positive association expectations in an organization can improve employees' knowledge sharing attitudes. Therefore, PT PLN (Persero) UIP JBT is advised to strengthen the culture of knowledge sharing by increasing social trust and providing appreciation to individuals who actively share information.